2021
DOI: 10.1002/smtd.202100054
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Structure of Low‐Dimensional Halide Perovskite through a Room Temperature Solution Process: Role of Ligands

Abstract: In this study, halide perovskite nanocrystals are synthesized by controlling the ligand length and amount, and investigated the effects on the change in the ligand length and amount on the shape, size, crystal structure, and optical properties of the perovskite nanocrystals. The results reveal the tendency and respective effects of amine and acid ligands on perovskite nanocrystals. The amine ligands bind directly to the perovskite nanocrystals. Consequently, the amine ligands with longer chains interfere with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…8–12 However, due to their high defect-induced charge recombination rate, the average photoelectric conversion efficiency of current halide perovskite photodetectors is still lower than the requirement for practical application. 13 Up to now, in order to inhibit the carrier recombination and promote the density of photon-generated carriers, several strategies have been explored, such as optimizing the preparation process, 14 surface modification, 15 defect passivation, 13 and coupling surface plasmon or piezo-photoelectronic effects. 16–20…”
Section: Introductionmentioning
confidence: 99%
“…8–12 However, due to their high defect-induced charge recombination rate, the average photoelectric conversion efficiency of current halide perovskite photodetectors is still lower than the requirement for practical application. 13 Up to now, in order to inhibit the carrier recombination and promote the density of photon-generated carriers, several strategies have been explored, such as optimizing the preparation process, 14 surface modification, 15 defect passivation, 13 and coupling surface plasmon or piezo-photoelectronic effects. 16–20…”
Section: Introductionmentioning
confidence: 99%
“…Yoo et al investigated the impact of carboxylic acid and carboxylamine ligands on the size, shape, and crystal structure of CsPbBr 3 nanocrystals synthesized using LARP. 51 They found that changes in carboxylic acid length primarily affected the shape and crystal structure of the perovskite nanocrystals, while increasing the carboxylamine ligand length led to a decrease in nanoparticle size, with no significant impact on shape. Additionally, they demonstrated that carboxylic acid ligands directly bond to the perovskite nanocrystals, whereas carboxylamine ligands either directly or indirectly interact with the perovskite nanocrystals through amine ligands.…”
Section: Double Halide Perovskitementioning
confidence: 99%
“…Ligands are typically required for colloidal ILHPs to stabilize the colloid and prevent undesired aggregations . Consequently, ligands, having interactions with ILHPs and themselves, become a critical factor to manipulate the self-assembly of colloidal ILHPs . It should also be mentioned that ligands can influence both the chemical and physical properties of ILHPs .…”
Section: Self-assembly Strategiesmentioning
confidence: 99%
“…63 Consequently, ligands, having interactions with ILHPs and themselves, become a critical factor to manipulate the self-assembly of colloidal ILHPs. 64 It should also be mentioned that ligands can influence both the chemical and physical properties of ILHPs. 28 To date, various types of ligands, including small molecules, 40 polymers, 41 and surfactants, 42 have been used to assist the self-assembly of colloidal ILHPs, yielding unique micro-/nanostructures.…”
Section: Self-assembly Strategiesmentioning
confidence: 99%